Patient-Derived Organoid Facilitating Personalized Medicine in Gastrointestinal Stromal Tumor With Liver Metastasis: A Case Report - Cao, Ying; Zhang, Xi; Chen, Qianyun; Rao, Xi; Qiu, Enming; Wu, Gang; Lin, Yu; Zeng, Ziqi; Zheng, Bin; Li, Zhou; Cai, Zhai; Wang, Huaiming; et al. (Frontiers in Oncology, 2022)
The gastrointestinal stromal tumor(GIST) is a rare gastrointestinal tract malignancy. The two main gene mutation sites are mutations in the tyrosine kinase receptor(KIT) and platelet-derived growth factors-α(PDGFR-α). KIT p.V560E is a point mutation within the exon 11 of KIT which has not been reported. Patient-derived organoids(PDOs) are novel in vitro 3D cultures of tissues from original patients which could identify sensitivity toward specific targets in patients with tumors and allow for personalized medicine when no guidelines-recommended molecular target therapy to novel genetic locus mutations are available. We encountered a 68-year-old patient who complained of diffused abdominal pain and intermittent melena lasting more than 10 days. He has no other gastrointestinal abnormalities, prior abdominal surgery or special family history. Surgery was conducted first to remove the lesions and ascertain the disease through pathological and immunohistochemical stains of the mass. Immunohistochemistry revealed that the tumor was positive for CD117 and Dog-1. Based on the above findings, he was diagnosed with GISTs. Meanwhile, we performed gene detection and organoid culture to support clinical decisions. KIT p.V560E and the reduced number of RB1 copies were two obvious mutations, so we adopted the first-line treatment imatinib 400mg/d. However, progressive disease prompted us to switch to sunitinib and his condition gradually improved. Meanwhile, our organoid culture showed sensitivity to sunitinib and tolerance to imatinib with IC50 values of 0.89nM, ＞20nM respectively. In summary, for the first to the best of our knowledge, the established organoid culture indicated the GISTs organoid could identify the sensitivity to target therapies and facilitate individual-based treatment.